LINGUOCOGNITIVE FEATURES OF PRECEDENT UNITS IN ADVERTISING TEXTS - Allaberganova Nilufar Matnazar qizi (Scholar Express Journal, 2025)
This article analyzes the use of precedent units in advertising texts - that is, familiar expressions and text units taken from a cultural, historical, literary or political context. The role of precedent units in advertising communication in attracting attention, instilling trust and increasing effectiveness is revealed. The article also studies the functional approach to these units, their significance in linguistics and intercultural communication, and their contribution to modern advertising styles.
Keywords: Precedent units; advertising discourse; cultural context